A revision of the mealybug genus Mirococcopsis Borchsenius (Homoptera: Coccinea: Pseudococcidae) based on the structure of the adult females - Gavrilov, Ilya A. (Zootaxa, 2007)
Eleven species of the genus Mirococcopsis Borchsenius, 1948, including a new species Mirococcopsis kalaginae Gavrilov, are revised and illustrated. Lectotypes of M. avetianae Ter-Grigorian, 1964, M. borchsenii (Ter-Grigorian, 1964a), and M. rubida Borchsenius, 1948 are designated. In addition, Eumirococcus Ter-Gregorian, 1964a, syn. nov. is considered a synonym of Mirococcopsis Borchsenius, 1948; Liucoccus Borchsenius, 1960 is considered a subgenus of Mirococcopsis, and M. brevipilosa Matesova, 1982, syn. nov. is considered a synonym of M. ammophila Bazarov & Nurmamatov, 1975. Due to the presence of very characteristic oral collar tubular ducts on M. stipae Borchsenius, 1949, this species is transferred to the genus Volvicoccus Goux, 1945: V. stipae (Borchsenius), comb. n. Some aspects of the morphology of Mirococcopsis and of other related genera, combined here in a group of Cryptoripersia Cockerell in Ehrhorn, 1899, are briefly discussed.